Pengembangan Motif Batik Girilayu sebagai Strategi Revitalisasi untuk Produk Fesyen Melalui Workshop dan Sosialisasi - Nurcahyanti, Desy; Najma Mumtaza Ghoutsin Nada; Annisa Meiliana Dewi; Arsi Gardatami (Universitas Muhammadiyah Manado, 2024)
This community service aims to develop new Girilayu Batik motifs that combine traditional elements with modern designs, and apply them to fashion and home decor products. Through a series of stages, starting from motif development, prototyping, to market testing, this Community Service has succeeded in producing products that are well received by consumers. The results of the market test show that this new motif not only increases the aesthetic appeal but also the selling value of Girilayu Batik products. The training provided to batik artisans improves their skills in applying new motifs, as well as involving the younger generation in preserving the batik tradition. Marketing strategies through digital catalogs, company profile videos, and other digital platforms have proven effective in expanding market reach. However, this community service identified challenges in technology adaptation by artisans and international market penetration. Overall, motif innovation and product diversification are important strategic steps to maintain the relevance and competitiveness of Girilayu Batik in an increasingly competitive market.